(untitled) (Journal of Parents and Teachers, 2026)
The role of the tutor is becoming increasingly important, and their support is essential in providing academic and career guidance to students. We propose a ‘general’ bibliography on the tutor rather than one that is ‘specific’ to each activity they perform. In other words, both their “functions” and ‘activities’ in general are the direct subject of these books.